The last holiday : a memoir - Scott-Heron, Gil, 1949-2011 (Grove Press, 2012)
A personal account by the late musician and poet traces the story of his life, career, and history-making 1981 tour at the side of Stevie Wonder to raise support for the establishment of Martin Luther King, Jr. Day.